STRATEGI PENDAYAGUNAAN DANA ZAKAT DAN INFAK PADA PROGRAM BEDAH RUMAH DI LAZISMU BANYUMAS - Enggal Meta Aribah; Ma’ruf Hidayat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze strategies for utilizing zakat and infaq funds in the house renovation program in Lazismu Banyumas. House renovation is an important initiative program in improving the quality of life of people with low incomes. However, the effectiveness of this program is very dependent on the proper utilization of zakat and infaq funds. This research uses a qualitative method with a case study approach at the Lazismu Banyumas institution. Data collection techniques were carried out through in-depth interviews, observation and analysis of related documents. Primary data was generated through interviews with distribution managers, house surgery teams and related mustahik. Observations were carried out by visiting the Amil Zakat Muhammadiyyah Banyumas Institute directly to observe procedures and strategies for utilizing zakat and infaq funds.The research results show that the strategy for utilizing funds includes worker selection, Minimizing labor maximizing materials, building material selection, building design and ongoing monitoring and evaluation. This research concludes that to increase the success rate of the house renovation program, it is necessary to implement an integrated, transparent and participatory strategy in utilizing zakat and infaq funds. It is hoped that these findings can contribute to the development of the best strategy for utilizing zakat and infaq funds in the future.